Coco as a Dominating Woman in Wei Huis Shanghai Baby - BAGUS NATA PRADEKSA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Abstract Shanghai Baby is one of well known literary works written by Zhou Wei Hui. The story in the novel told about a woman named Coco who fought against some problems concerning her love life. This research focused on Coco’s domination and the relationship between her and her two men, TianTian and Mark by using Carl Jung’s libido and Anthony Giddens’ transformation of intimacy. This study proposes two statements of the problem: 1. How is Coco as a dominating woman depicted in Shanghai Baby? 2. How does Cocos domination influence the male characters in the novel? The purposes of this study are to explain how Coco as a dominating woman is depicted in Shanghai Baby and to explain how her domination influences the male characters in the novel. The data source of this study was the novel written by Wei Hui titled Shanghai Baby. The main data was taken from the data source which depicts Coco’s domination and its influence to the male characters. The main data was analyzed by using theoretical framework. This research is a qualitative study. Researchers use psychological approach to analyze the psychological issues in the novel and use a sociological approach to analyze the relations between the main character and the male characters. . The results of this study showed that Coco was a strong and independent woman who owned two men, TianTian and Mark. TianTian was the man who fulfilled Coco’s love desire and Mark was the man who fulfilled Coco’s sexual desire. Coco’s domination gave TianTian an anxiety of losing her and gave Mark an advantage to explore the Asian beauty of Coco’s. Keywords: libido, love, sex, passionate, romantic Abstrak Shanghai Baby merupakan salah satu karya sastra populer karangan Zou Wei Hui. Novel tersebut menceritakan tentang seorang wanita bernama Coco yang berjuang dalam kisah cintanya sendiri. Penelitian ini berfokus pada dominasi Coco dan hubungannya dengan dua pria dalam hidupnya, yaitu TianTian dan Mark dengan menggunakan teori libido oleh Carl Jung dan buku yang berjudul The Transformation of Intimacy karangan Anthony Giddens. Terdapat dua rumusan masalah dalam studi ini: 1. Bagaimana dominasi Coco digambarkan dalam Shanghai Baby? 2. Bagaimana pengaruh dominasi Coco terhadap tokoh pria di dalam novel? Tujuan dari studi ini adalah untuk menggambarkan dominasi Coco dan bagaimana pengaruhnya terhadap tokoh pria di dalam novel. Sumber data studi ini adalah novel karya Wei Hui yang berjudul Shanghai Baby. Data inti diambil dari sumber data yang menggambarkan dominasi Cocodan pengaruhnya terhadap tokoh pria. Data inti dianalisis dengan menggunakan teori yang sudah disebut sebelumnya. Penelitian ini menggunakan metode kualitatif. Peneliti menggunakan pendekatan psikologi untuk menganalisis masalah psikologi dalam Shanghai Baby dan pendekatan sosiologi untuk menganalisis hubungan tokoh utama dengan tokoh pria dalam novel. Hasil dari studi ini menunjukkan bahwa Coco adalah seorang wanita yang kuat dan mandiri yang memiliki dua pria, TianTian dan Mark. TianTian merupakan cinta romantiknya, sedangkan Mark adalah cinta birahinya. TianTian adalah pria yang memberi Coco keindahan cinta, sedangkan Mark adalah pria yang memberi Coco kepuasan seksual. Dominasi Coco membuat TianTian takut kehilangan Coco, sedangkan pengaruh dominasinya terhadap Mark yaitu Mark berkesempatan untuk menikmati kecantikan Asia yang dimiliki Coco. Kata kunci: libido, cinta, birahi, romantik